Aerosol delivery of star polymer-siRNA nanoparticles as a therapeutic strategy to inhibit lung tumor growth. (June 2022) - Ma, Z.; Wong, S.W.; Forgham, H.; Esser, L.; Lai, M.; Leiske, M.N.; Kempe, K.; Sharbeen, G.; Youkhana, J.; Mansfeld, F.; Quinn, J.F.; Phillips, P.A.; et al.
Abstract: Lung cancer is a major contributor to cancer-related death worldwide. siRNA nanomedicines are powerful tools for cancer therapeutics. However, there are challenges to overcome to increase siRNA delivery to solid tumors, including penetration of nanoparticles into a complex microenvironment following systemic delivery while avoiding rapid clearance by the reticuloendothelial system, and limited siRNA release from endosomes once inside the cell. Here we characterized cell uptake, intracellular trafficking, and gene silencing activity of miktoarm star polymer (PDMAEMA-POEGMA) nanoparticles (star nanoparticles) complexed to siRNA in lung cancer cells. We investigated the potential of nebulized star-siRNA nanoparticles to accumulate into orthotopic mouse lung tumors to inhibit expression of two genes [βIII-tubulin, Polo-Like Kinase 1 (PLK1)] which: 1) are upregulated in lung cancer cells; 2) promote tumor growth; and 3) are difficult to inhibit using chemical drugs. Star-siRNA nanoparticles internalized into lung cancer cells and escaped the endo-lysosomal pathway to inhibit target gene expression in lung cancer cells in vitro. Nebulized star-siRNA nanoparticles accumulated into lungs and silenced the expression of βIII-tubulin and PLK1 in mouse lung tumors, delaying aggressive tumor growth. These results demonstrate a proof-of-concept for aerosol delivery of star-siRNA nanoparticles as a novel therapeutic strategy to inhibit lung tumor growth. Graphical abstract: Image 1